2013
DOI: 10.1186/2251-7715-2-6
|View full text |Cite
|
Sign up to set email alerts
|

Application of rural slaughterhouse waste as an organic fertilizer for pot cultivation of solanaceous vegetables in India

Abstract: Purpose Improving the nutritional value of rice straw by microbial inoculants and some physical treatments for animal feeding during dry seasons. Methods Different microbial inoculants and some physical treatments were used to improve the nutritional value of rice straw. Rice straw was divided into moist straw, soaked straw for 24 h without pasteurization and soaked for 24 h and pasteurized at 100 °C/1 h, and all of them were inoculated with different microbial inoculants. Results Moistened rice straw inoculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 23 publications
2
27
2
1
Order By: Relevance
“…Similarly, Tu et al (2006) observed that microbial biomass and activity were higher in organically managed soils compared to conventional soil amendment with synthetic inorganic fertilizer. In a more recent study, Roy et al (2013) reported rapid released of available plant nitrogen in organic fertilizer produced from bovine-rumenblood-digesta mixture (BBRD).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Tu et al (2006) observed that microbial biomass and activity were higher in organically managed soils compared to conventional soil amendment with synthetic inorganic fertilizer. In a more recent study, Roy et al (2013) reported rapid released of available plant nitrogen in organic fertilizer produced from bovine-rumenblood-digesta mixture (BBRD).…”
Section: Discussionmentioning
confidence: 99%
“…Additional components of the experimental fertilizers were chemically pure magnesium sulphate (MS) (POCH company) and/or blood meal (BM) [9]. All components of experimental fertilizers were dried in 105 °C prior to use.…”
Section: Methodsmentioning
confidence: 99%
“…However, agricultural performance assessments are very rare and generally focus on vegetable and forage crops (Roy et al, 2013).…”
Section: Introductionmentioning
confidence: 99%